Intravitreal Ranibizumab Had Limited Effect on Cystoid Macular Edema Due to Albumin-Bound Paclitaxel: A Case Report and Literature Review - Ye, Suna; Fang, Qiqi; Yao, Jinyu; Xing, Jianqiang; Tang, Shibo; Ma, Jacey Hongjie (Frontiers in Oncology, 2021)
Angiographically silent macular cystoid edema (CME) is a rare complication from nab-paclitaxel. Here, we report a 45-year-old woman with breast cancer who developed cystic macular edema after several months of treatment with nab-paclitaxel. With cessation of nab-paclitaxel and intravitreal ranibizumab treatment, her macular edema did not improve. Then, brinzolamide eye drops were prescribed and one month later her vision improved and macular edema was significantly reduced. Finally, we review other cases of macular cystoid edema induced by nab-paclitaxel that have been reported in the literature and discuss the underlying pathogenesis of nab-paclitaxel-induced CME.